Risk assessment analysis of potato genotype susceptibility to water rot-causing oomycetes. (January 2019) - Yellareddygari, S.K.R.; Taylor, Raymond J.; Pasche, Julie S.; Gudmestad, Neil C.
Abstract: Water rots are a group of important potato tuber rot diseases such as pink rot, Phytophthora tuber rot, and leak caused by the oomycete pathogens Phytophthora erythroseptica, P. nicotianae, and Pythium ultimum, respectively. If not managed, these diseases either alone or in combination, can cause severe yield loss and substantial reductions in quality. Growers continue to rely on fungicides for water rot management in the field and during post-harvest storage. Previous and ongoing breeding attempts have failed to identify and develop commercially acceptable potato cultivars resistant to all three diseases. This is mainly due to the complex, expensive, and time-consuming methodologies required to screen for susceptibility to water rot pathogens. Currently, potato genotypes are assessed for susceptibility to individual water rot pathogens which is labor intensive. Considerable savings in time and effort would be realized if potato genotypes could be evaluated for susceptibility to one water rot pathogen and then statistical analysis applied to determine the probability of the reaction of a genotype to the other rot pathogens. A proportional odds model was fitted to examine the risk of genotype screening outcome (ordinal) to understand the relationships among water rot causing oomycetes in potato. Compared to P. erythroseptica, P. ultimum infected genotypes having susceptibility risk was high (2.6) versus other cultivar susceptibility categories. Potato genotypes screened for P. nicotianae have a significant susceptibility risk decreased by 38% when compared to P. erythroseptica . Highlights: Proportion odds model is used to model ordinal outcome. Risk of potato genotype screening outcome was used to understand the relationship between water rot pathogens. Compared to Phytophthora erythroseptica, Pythium ultimum infected genotypes have high susceptibility risk.